Ecological-Industrial Problems while Realizing the Strategy for the Development of a Large Agro-Industrial Manufacture Sector In the National Food Supply System - Mikhail A. ANANIEV; Tatiana I. TEPLUKHOVA (Communications of International Proceedings, 2021)
The article discusses the ecological-industrial problems emerging while implementing the development strategy for the large agricultural manufacture sector in the national food supply system of the Russian Federation. The authors propose the main directions for improving the mechanism of managing the development of the sector of a large agro-industrial manufacture in the national food supply system, including from the perspective of the management system.
Keywords: National Food Supply System; Large Agro-Industrial Manufacture Sector; Ecological-Industrial Problems; Environmentally Friendly Production.